How young workers get their training : a survey of Germany versus the United States - Winkelmann, Rainer [Verfasser] (My University, 1997)
"The recent economic literature on the incidence of various forms of post-secondary on-the-job and off-the-job training in Germany and the United States, as well as on the effects of training on wages, inequality, an labor mobility is surveyed. Young workers in Germany receive substantially more company based (apprenticeship) training than United States workers. In the United States, high turnover deters firms from investing in general skills while it results in improved job matches. The received literature consents that key institutional elements required to make the German apprenticeship system work are absent in the United States." (author's abstract, IAB-Doku) ((en)) Der Beitrag gibt einen Literaturüberblick über die Systeme der Berufsausbildung in Deutschland und den USA. Dabei werden auch die Auswirkungen auf Löhne und berufliche Mobilität betrachtet. (IAB)
Keywords: S System beruflicher Bildung; S 1.3 Berufliche Erstausbildung; G 1.3.3.3 Mobilität; G 2.3.1 Arbeitsteilung & -organisation; L 2.1.3 Erfahrungslernen; L 2.1.1 Informelles Lernen; I 2.3.2 Nordamerika; Berufsbildungssystem; Internationaler Vergleich; Betriebliche Berufsausbildung; Bildungsertrag; Berufliche Mobilität; On-the-job training; USA